The relationship between social media marketing activities and brand equity with the mediating role of consumer’s benefits and experience on luxury beauty - Hediana, Bianca; Astuti, Rifelly Dewi (Kemakmuran Hijau: Jurnal Ekonomi Pembangunan, 2025)
Background: The rapid growth of the beauty industry and the increasing number of luxury goods consumers in Indonesia have made social media marketing a crucial tool for brands in the beauty sector. Understanding the relationship between social media marketing activities and consumer-based brand equity can provide valuable insights for businesses looking to maximize their brand's presence and engagement on social media platforms. Methods: This study examines the impact of social media marketing activities on consumer-based brand equity, with social media benefits and brand experience as mediating variables. Data was collected through a 5-point Likert scale questionnaire distributed to 471 respondents, aged 25-44 years, who purchase and follow luxury beauty brands on social media. The data was analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique to evaluate direct and mediating effects. Findings: The study reveals a significant direct and mediating effect of social media marketing activities on consumer-based brand equity. Additionally, it finds a direct and mediating effect of social media marketing activities on social media benefits, indicating that effective marketing strategies can enhance both brand equity and the perceived benefits consumers derive from social media interactions with brands. Conclusion: This research demonstrates the importance of social media marketing activities in strengthening brand equity and enhancing social media benefits. The findings suggest that luxury beauty brands can improve their consumer relationships and brand perceptions by optimizing their social media strategies, with a focus on brand experience and benefits. Novelty/Originality of this article: This study contributes to the literature by highlighting the mediating role of social media benefits and brand experience in the relationship between social media marketing and consumer-based brand equity, particularly in the context of luxury beauty brands in Indonesia. The use of SEM-PLS provides a robust framework for understanding the complex dynamics of social media marketing in the beauty industry.